(3fbhd eNJdaIs
(3ChdgG (B:s
(3bhdg JYGdi (B:" (3cJH Ydjce GdUjGe (B" (3GdBjg bGd HYV GdYGQajf GdMceg ai GdUhe Cf ef YGOg GdNdb TQH GdCOhjI GdeSgdI s
(3BNQgG (B:s
(3hef jcSH NWjFI Ch EKeG Ke jQe HgG HQjFkG ai HGH GdBjI GdcQjeI ai bhdg JYGdi (B:" (3hdG jfabhfgG (B" (3Je s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B9s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3eUOQ GbJfGA GdCUd (B:s
(3GdeOQSI GdCMeOjI (B_ (3GdehUd (B(57) s
Keywords: (3GdeLGejYs